Frances in the country [book with audioplayer] - Scanlon, Liz Garton (VOX Books, 2022)
Frances is a spirited city kid itching to explore, but city walls aren't for climbing, city rooms aren't for running, and city parks are way too crowded. When she visits her cousins in the country, she finally gets her chance to roam, before inviting them to come visit her, too, where the city cats croon and city alleys echo and city streets beep and shine...